2017
DOI: 10.1186/s41935-017-0023-9
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of alcohol concentrations in samples referred to the forensic Laboratory in Baghdad

Abstract: Background: Detection of alcohol in postmortem blood and body fluids is of extreme importance in medico-legal investigation as it may affect and change the decision of the court in legal hearing. It can be a cause death or sharing a role in different modes of death. Objectives: To evaluate the problem of alcohol intake in general and its relation to age,sex and its contribution in different causes of death. Method: A prospective study within 6 month period on postmortem blood samples referred to the lab. For d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(10 citation statements)
references
References 7 publications
(6 reference statements)
0
10
0
Order By: Relevance
“…Descriptions of the studies are reported in Table 2. Of the included studies, only four were alcohol specific [17][18][19][20]; two were about substance use [21,22] and two about health risk behaviours [23,24]; one each was primarily focused on mental health disorders [25], smoking [26], novel psychoactive drugs [27], risky driving [28], and sleep disorders [29]. No literature was found that related to preventative strategies in relation to alcohol.…”
Section: Research Topicsmentioning
confidence: 99%
See 4 more Smart Citations
“…Descriptions of the studies are reported in Table 2. Of the included studies, only four were alcohol specific [17][18][19][20]; two were about substance use [21,22] and two about health risk behaviours [23,24]; one each was primarily focused on mental health disorders [25], smoking [26], novel psychoactive drugs [27], risky driving [28], and sleep disorders [29]. No literature was found that related to preventative strategies in relation to alcohol.…”
Section: Research Topicsmentioning
confidence: 99%
“…Only one study recruited a sample from more than one province [25]. Four studies recruited from Baghdad [19][20][21]27] and Erbil [17,22,23,28]. Two recruited students from Karbala [18,26].…”
Section: Study Settings and Data Collectionmentioning
confidence: 99%
See 3 more Smart Citations